VD_FINDINFO ML / 2011 / 154 vom 16. August 2011 - VD Tribunal cantonal (2011)
MEILLEURE FORTUNE, EXCEPTIONMOYEN DE DÉFENSE, MOYEN DE DROIT, ACTION EN CONSTATATION | 265a al. 1 LP, 265a al. 4 LP, 63 CPC (CH)